Model of Shunting Technology Based on System Structure - Pepevnik, Anton (Promet - Traffic&Transportation, 2003)
Railway transport is facing a growing liquidity problem.The major problem in small systems is the detention of wagonsat marshalling yards, which prolongs the time of freight travel.To avoid this problem it is of great importance to search for parametersthat would enable creation of a model of technologythat would provide shorter wagon detention time at stations aswell as optimising the number of marshalling yards for smallsystems. It is at the same time a great opportunity to search for alink between the shunting work in the railway transport and thetheoretical system approach which presents it as a current scientificproblem. In classical technology the shunting work iscarried out with no application of and no regard for the systemapproach. With new shunting systems in the railway transportthe regard for theory of transport systems is crucial as the secondarylevel of classical methods.As already pointed out, from the theoretical point of viewan important contribution will be made to the use of system theoryfor shunting purposes, since the suggested model effectivelyprovides the approach of analysing separate elements in therailway transport structure into integral shunting operations atthe railway stations.